3x+6py-7=0

Simple and best practice solution for 3x+6py-7=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6py-7=0 equation:


Simplifying
3x + 6py + -7 = 0

Reorder the terms:
-7 + 6py + 3x = 0

Solving
-7 + 6py + 3x = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 6py + 7 + 3x = 0 + 7

Reorder the terms:
-7 + 7 + 6py + 3x = 0 + 7

Combine like terms: -7 + 7 = 0
0 + 6py + 3x = 0 + 7
6py + 3x = 0 + 7

Combine like terms: 0 + 7 = 7
6py + 3x = 7

Add '-3x' to each side of the equation.
6py + 3x + -3x = 7 + -3x

Combine like terms: 3x + -3x = 0
6py + 0 = 7 + -3x
6py = 7 + -3x

Divide each side by '6y'.
p = 1.166666667y-1 + -0.5xy-1

Simplifying
p = 1.166666667y-1 + -0.5xy-1

Reorder the terms:
p = -0.5xy-1 + 1.166666667y-1

See similar equations:

| y-11=-10 | | (5p^3)(-m^8p^2)= | | -5x+17=-20x-18 | | p=s-14 | | 36x+200=76x | | x-11=5x | | 12x-4=96x-12 | | y=3x+-8 | | 4(x-y)(x-y)-25= | | 26x+9=8x+39 | | b+10=-13 | | 8=vu | | 3a-3=4a-1.5 | | x^2-18=19 | | (9-y)(4y+6)=0 | | 17+26x=30 | | -2x^2-x-3=0 | | 14-t=-10 | | 8.26x+4=68.2276+2x | | y=-.2x+12 | | 14.95-7.55= | | 13-k=5 | | 3/4x-7/4=8 | | 14r+12r=832 | | 9x+2=27x | | 5.7(x-1)=-0.3+42.3 | | -3y-2=-2y | | -7x^3*8x^2= | | 9x^2+24x=9 | | 5m^2=112+8m | | p^2+3p^3-3p-1=0 | | 11-x+3=3n+3n |

Equations solver categories